2021
DOI: 10.1002/celc.202100013
|View full text |Cite
|
Sign up to set email alerts
|

Derived CuSn Alloys from Heterointerfaces in Bimetallic Oxides Promote the CO2 Electroreduction to Formate

Abstract: Electroreduction of CO 2 into valuable chemicals provides a promising strategy for mitigating excessive CO 2 emissions and storing intermittent renewable energy. Herein, SnO 2 /CuOnanoparticle composites (NCs) with rich heterointerfaces were designed for selectively converting CO 2 into liquidus formate. Distinct from only monometallic phase evolved in physicallymixed samples, Cu and Sn atoms at the heterointerfaces were in-situ reduced into alloys under working conditions. With residual SnO x /CuO x stabilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For instance, He and co-workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems. [19] More recently, works have continued this topic using SnÀ PbÀ Sb alloy foil, [20,21] nanoporous CuÀ Ag alloys, [22] CuÀ Sn alloys, [23][24][25][26] SnÀ Sb alloys, [27] CuÀ Sb alloys, [28] CuÀ Bi amorphous bimetallic electrocatalysts, [29] or InÀ Sn alloy core-shell nanoparticles. [30] Tin and bismuth are the most studied metals for the CO 2 RR towards formic acid/formate and, with respect to them, recent bimetallic studies have revealed that the Bi presence improves the performance of Sn catalysts, [31,32] although pure Bi catalysts outperform those combining Sn and Bi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, He and co-workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems. [19] More recently, works have continued this topic using SnÀ PbÀ Sb alloy foil, [20,21] nanoporous CuÀ Ag alloys, [22] CuÀ Sn alloys, [23][24][25][26] SnÀ Sb alloys, [27] CuÀ Sb alloys, [28] CuÀ Bi amorphous bimetallic electrocatalysts, [29] or InÀ Sn alloy core-shell nanoparticles. [30] Tin and bismuth are the most studied metals for the CO 2 RR towards formic acid/formate and, with respect to them, recent bimetallic studies have revealed that the Bi presence improves the performance of Sn catalysts, [31,32] although pure Bi catalysts outperform those combining Sn and Bi.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, He and co‐workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems [19] . More recently, works have continued this topic using Sn−Pb−Sb alloy foil, [20,21] nanoporous Cu−Ag alloys, [22] Cu−Sn alloys, [23–26] Sn−Sb alloys, [27] Cu−Sb alloys, [28] Cu−Bi amorphous bimetallic electrocatalysts, [29] or In−Sn alloy core‐shell nanoparticles [30]…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Nevertheless, limited by their poor CO 2 activation capability and low intrinsic conductivity, SnO 2 -based electrocatalysts usually exhibit unsatisfactory Faraday efficiency (FE) and current density for formate generation. 11,12 The construction of oxygen vacancy (O v ) defects has been certified as an effective route to increase the intrinsic activity of electrocatalysts by optimizing the adsorption energy of catalytic intermediates. 13,14 This is because O v can change the surface electronic structure of SnO 2 , which ensures fast electron transfer by increasing the carrier density and reducing the band gap of SnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, CO 2 can be reduced to many different products such as CO, methane, ethylene, formic acid, acetic acid, ethanol, and n-propanol, depending on the electrolysis voltage applied and electrode materials/electrocatalysts used. [9][10][11][12][13][14] A good catalyst is thus desirable to achieve good selectivity on those value-added products.…”
Section: Introductionmentioning
confidence: 99%